Global Branding of Religious Education: Islamic Green Schools in Achieving the SDGs - Siti Rohmatin Kusbah; Khozin Khozin (Urwatul Wutsqo: Jurnal Studi Kependidikan dan Keislaman, 2025)
This study examines the Islamic Green School concept as a branding strategy for Islamic schools based on Islamic moderation and Sustainable Development Goals (SDGs). The global environmental crisis demands that Islamic education not only focus on rituals and memorization but also instill ecological awareness as an integral part of Islamic values. Through a qualitative approach based on literature review, this research analyzes institutional branding strategies, implementation challenges, and the contribution of Islamic Green Schools to achieving the SDGs, particularly SDGs 4, 12, 13, and 15. The findings reveal that Islamic Green Schools can integrate the values of khalifah fil ardh with sustainable educational practices through three main strategies: strengthening universal Islamic values and sustainability, curriculum innovation based on ecology, and model scalability through sharia and SDG collaboration. However, implementation faces challenges, including low SDG literacy, curriculum fragmentation, limited resources, and ideological resistance. This study recommends strengthening teacher capacity, government policy support, and developing data-based monitoring systems to reinforce authentic and sustainable branding